The Role of Islamic Education in Building the Moral and Spiritual Values of the Younger Generation - Lina Luthfiyyah (Rahis Cendekia Indonesia, 2025)
The moral and spiritual development of the younger generation has become a major concern in the modern era, particularly in the midst of rapid globalization, technological advancement, and shifting social values. These changes have brought significant challenges to young people, including moral degradation, identity confusion, and declining spiritual awareness. Education, therefore, is expected not only to develop intellectual competence but also to shape character and inner values. In this context, Islamic education plays a crucial role in guiding the younger generation toward moral integrity and spiritual consciousness through a holistic educational framework rooted in Islamic teachings. Islamic education emphasizes the integration of faith (iman), knowledge (ilm), and practice (amal), which collectively contribute to the formation of balanced individuals who are ethically responsible and spiritually aware. This study aims to explore and analyze the role of Islamic education in building the moral and spiritual values of the younger generation by examining relevant theoretical perspectives and empirical findings from previous studies. The research employed a qualitative approach using a library research (literature review) design. Data were collected from primary and secondary sources, including classical and contemporary Islamic educational texts, peer-reviewed journal articles, research reports, and authoritative documents related to moral education, spirituality, and youth development. The collected data were analyzed using descriptive-analytical techniques by identifying key themes, concepts, and patterns related to the moral and spiritual objectives of Islamic education. The findings of the study reveal that Islamic education significantly contributes to moral development by instilling core ethical values such as honesty, discipline, responsibility, justice, respect, and compassion. These values are internalized through instructional content, teacher exemplification, and religious practices embedded in the educational process. In addition, Islamic education fosters spiritual development by strengthening learners’ relationship with Allah through worship, reflection, and moral self-awareness, which in turn enhances emotional stability, self-control, and a sense of life purpose. However, the study also highlights several challenges, particularly when Islamic education is implemented in a predominantly theoretical manner with limited emphasis on experiential learning and contextual application. In conclusion, the study affirms that Islamic education plays a vital role in shaping the moral and spiritual character of the younger generation when it is implemented comprehensively and contextually. Strengthening pedagogical approaches, educator competence, and supportive learning environments is essential to maximize the transformative potential of Islamic education. By maintaining its core values while responding to contemporary challenges, Islamic education can contribute to the development of a generation that is morally grounded, spiritually resilient, and capable of contributing positively to society.